Interreligious Dialogue: Facing the Next Frontier - Thomas, K. (Journal of Dharma, 1985)
The volume contains eleven essays on the need for the West to enter into an interreligious dialogue with the East. The editor provides in the beginning an overview of the essays. He points out that in the contemporary theological world in the West, there is an overwhel- ming consensus that everyone, including Christians, has to re-examine and re-evaluate older attitudes towards other world religions. It is this consensus that underlies the phrase in the title of this book, "The Next Frontier" (p. viii).